PENGARUH INTELLECTUAL CAPITAL DAN PROFIT SHARING RATIO TERHADAP PROFITABILITAS 14 PERBANKAN SYARIAH DI INDONESIA - maryana; cut muftia keumala; Irfan; Muzakir (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2023)
This study aims to examine the effect of intellectual capital and profit sharing ratio on the profitability of Islamic banking in Indonesia. The data used in this study is secondary data as many as 30 samples using purposive sampling method. The method used to analyze the independent variable and the dependent variable is the multiple linear regression method and the classical assumption test. The results of the research partially intellectual capital have a significant effect on profitability in Islamic banking in Indonesia and the variable profit sharing ratio has a significant effect on profitability in Islamic banking in Indonesia. Simultaneously shows that intellectual capital and profit sharing ratio simultaneously have a significant effect on profitability in Islamic Banking in Indonesia. Keywords: intellectual capital, profit sharing ratio and profitability